Analisis Proyeksi Keuangan melalui 2P (Pay for Perfomance dan Pay for Position) dalam Penyejahteraan Pegawai di Pondok Pesantren Darullughah Wal Karomah - Ainur Rifqi; Mohammad Syahidul Haq (Kelola: Jurnal Manajemen Pendidikan, 2023)
The quality of human resource performance was influenced by the welfare of human resources that can be provided as salaries/income to employees. Several theories are used to determine employee salaries or income, including pay for performance and position theory. In determining employee salaries, reasonable financial projections are needed in educational institutions. One projection method that can be used is the Capital Budgeting method, utilizing a profitability index model. The method used in this study is descriptive analytics by using a profitability index model to calculate projections and considering Pay for Performance and Pay for Position on pesantren expenditure items. The subject of this study was the management of Darullughah Wal Karomah Islamic Boarding School, namely the head, treasurer, head of staffing, and principal under the auspices of the pesantren with stages of data collection through interviews and document studies, implementation of analysis, and focus group discussion. Based on the calculation of pay for performance and pay for position and combined with the results of calculating the profitability index, it was found that the form of awards in the form of income that is suitable for use by pesantren is the use of pay for position theory for pesantren administrators and pay for performance for teachers and education staff. The results of this research can be used as a basis for Islamic boarding schools to compile guidelines for providing income to employees.